Answer:
$92,107 = Equity at the end
Step-by-step explanation:
Given that,
Beginning assets = $259,000
Beginning equity = $194,250
Increase in assets = $80,000
Increase in liabilities = $52,643
Therefore,
Accounting equation is as follows:
Total Assets = Total liabilities + Stockholders equity
(Beginning assets + Increase in assets) = [Increase in liabilities + (Beginning equity + equity at the end)]
($259,000 + $80,000) = [$52,643 + ($194,250 + Equity at the end)]
$339,000 - $246,893 = Equity at the end
$92,107 = Equity at the end